KONSTRUKSI PENGAWASAN INDEPENDEN UNTUK MENCEGAH TINDAK PIDANA PUNGUTAN LIAR DALAM PELAYANAN PUBLIK - Pandji Ndaru Sonatra; Widodo Tresno Novianto; Agus Riewanto (Masalah-Masalah Hukum, 2019)
This conceptual idea aims to conduct a study of the prevention of criminal acts of illegal levies to realize good governance. This conceptual idea examines issues regarding what are the factors that lead to the ineffectiveness of the surveillance system in preventing illegal acts of crime in public services. The ineffectiveness of the supervision system is due to the lack of direct supervision during the transaction process between service users and the apparatus, the absence of special laws governing criminal acts of illegal levies, and the existing supervisory system has not been built integrally. In order to prevent criminal acts of illegal levies, the construction of an independent supervisory institution model is needed, whose main task and function is to provide witnesses in all transactional activities for the effectiveness of public services.